A Sensitive Spectral Survey of Interstellar Features in the Near-UV [3040-3700Å]. Issue Volume 9:Issue S297(2013) (21st February 2014) - Bhatt, N. H.; Cami, J.
Abstract: We present a comprehensive and sensitive unbiased survey of interstellar features in the near-UV range (3040-3700 Å). We combined a large number of VLT/UVES archival observations of a sample of highly reddened early type stars – typical diffuse interstellar band (DIB) targets. We stacked the individual observations to obtain a spectrum with a signal-to-noise ratio exceeding 1500. Careful inspection of this spectrum reveals tens of absorption features of interstellar nature, most of which can be identified with various atomic and molecular features. We furthermore detect four weak unidentified features, but we cannot establish their interstellar nature. Our sensitivity is limited by telluric and instrumental residuals; this precludes us from detecting broader features (e.g. DIBs). For each detected feature, we measured fundamental parameters (radial velocities, line widths, and equivalent widths). We also compare our co-added spectrum to cold gas-phase laboratory measurements of small, neutral polycyclic aromatic hydrocarbon (PAH) molecules.